ACP-EU fisheries - Market and trade: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
In the last years ACP countries have shown a growing focus on enhancing the contribution of the fisheries sector to national development, where different actions have been taken either to strengthen the development of small-scale fishing activities and of local value-added processing linked to industrial or semi-industrial fishing activities or to secure improved access to national exclusive economic zones (EEZs). Given that the EU remains the major market for ACP fisheries exports, this Executive Brief presents the main EU policy developments in 2012-13, such as the reform of the Common Fisheries Policy (CFP), the new sustainable fishing legislation and the implementation of the EU Regulation to combat IUU fishing. It further examines the developments of ACP-EU relations on fisheries (including the EPAs agreements), and the policy developments in the ACP on enhancing the contribution of the fisheries sector to national development. Finally, the Brief discusses a number of market access-related issues of concern to ACP governments, including the growing importance of sustainability standards and requirements, the application of rules of origin, and the new market opportunities in China.